Technology readiness towards implementation of e-learning: a case study at Terengganu Advanced Technical Institute (TATI) / Zainudin Othman - Othman, Zainudin (2006)
E-learning becomes important to the organization for future investment and the competition in education markets has encouraged TATI to consider it in order to enhance learning. This study focused on self-development, technology and innovation readiness in TATI. The motivation of this study is due to the fact that, literatures showed a little evidence of e-learning readiness in many organizations. Thus TATI is selected as organization for research in this area. There are three sections of research questions in the questionnaire that is selfdevelopment, technology and innovation. The questionnaire has been designed based on five-point Likert scale, which ranging from Strongly Disagree to Strongly Agree. The data were analyzed using SPSS, version 12.0. The questionnaires were distributed to the whole TATI lectures. This represents that 99 respondents which directly involved in teaching. Out of 99 questionnaires distributed only 60 respondents had returned. The study revealed that lecturer is ready to attend trainings and prefer to spend time for self study. They are able to use computer and access the internet any time and any place. Almost all lecturers have the computer and internet skills. They are ready in terms of adaptability with the barrier of innovation such as internal or external political or legal issues. The overall result showed that TATI's lecturers are ready to implement e-learning in the organization.